A atuação das Incubadoras de Tecnologia Social sob a ótica dos Empreendimentos Econômicos Solidários nos estados de Mato Grosso e Mato Grosso do Sul - DANIELA DA SILVA CARVALHO (2024)
This study develops a critical and reflective reading of the economic solidary enterprises as an alternative to the traditional economic model, based on an epistemological theoretical context that articulates the notions of solidary techno-science, Sustainable territorial development and solidarity popular economy. Based on the thesis that techno-science transcends the theoretical conceptual scope and when disseminated in a solidarity way, valuing the territory and its territorialities, it is configured as an agent of social and economic transformation providing opportunities for local development, from a growth model that is inclusive and sustainable, the researcher set out to investigate how social technology incubators influence the constitution of Popular Solidarity Economy (PSE) enterprises through the application of techno-science, considering the importance of rethinking local development practices from the knowledge and needs of the communities themselves. The general objective of the study was to understand the performance of social technology incubators from the perspective of Solidary Economic Enterprises (EES), analyzing the techno-science practices aimed at local development, as well as the benefits and challenges faced by the enterprises involved in these initiatives, broken down into specific objectives, such as a) Characterize the principles and values that guide the performance of social technology incubators in Solidary Economic Ventures; ) Report on the experiences of technoscience, emphasizing good practices and relevant learning for communities; c) Investigate the needs and demands of EES in the states of Mato Grosso and Mato Grosso do Sul, in relation to strengthening the popular and solidarity economy and promoting social and economic inclusion; d) Present guidelines to strengthen the role of techno-science and local development considering the specificities and demands of EES and its territorialities, seeking to structure guidelines that strengthen autonomy, the self-management and resilience of solidarity ventures. To understand these dynamics, the methodology adopted is based on oral history, valuing the narratives and knowledge of the participants. The choice of this methodology was fundamental to capture the complexity of the experiences and challenges faced by these enterprises, allowing the voices of participants to guide the theoretical and practical construction of the study. The data collection involved dialogues, in which participants reported their experiences, perceptions and strategies in the context of solidarity enterprises, highlighting the tensions and dilemmas that arise when trying to balance the demands of the system with the values of the solidarity economy. The reflections on the reports showed a scenario in which solidarity enterprises are often pressured to reproduce practices of traditional organizations, which limits their emancipatory potential and reinforces criticism of the capitalist system. Operating in an environment dominated by the logic of profit and competitiveness, many of these enterprises end up repeating models that do not conform to the principles of cooperation and social justice that underlie the solidarity economy and in most cases, guided and accompanied by social incubators that should propose the reverse movement. This study, then, presents a critical view of the traditional model and proposes the elaboration of guidelines/ propositions that encourage technoscience as a tool to rescue the autonomy and sustainability of solidarity enterprises. The framework of guidelines built throughout the research is flexible and can be adapted to the specificities of each territory, responding to local realities and valuing community knowledge. The proposals included seek to strengthen support and collaboration networks between enterprises, promoting a solidarity economy that respects the cultural and social diversity of territories and avoids dependence on conventional practices. Thus, the collaborative guidelines aim not only at improving management and production practices, but also at building an environment that favors solidarity, mutual support and integration of local knowledge. In the end, the general perceptions and contributions of the study reinforce the importance of understanding solidary technoscience as a transformative movement that challenges the hegemony of capitalism and proposes an inclusive and long-term development. This work represents a step towards a new economic model, focused on the well-being of communities and the sustainability of territories, seeking to integrate a decolonial practice that respects and values the knowledge, cultures and experiences of each community.